Implementation of the Child-Friendly City Policy through the Family Learning Center (Puspaga) Program in the City of Surabaya - Khotimah, Aas Nur; Wijayanti, Nurrul Fahmi Maulida; Permana, Ipik; Lestari, Aghnia Dian (PT FORMOSA CENDEKIA GLOBAL, 2024)
Children are often vulnerable to violence due to their limited knowledge and physical strength. The family, the environment, and the state must be responsible for the fulfillment of children's rights and child protection. The purpose of this study is to determine the suitability between the Family Learning Center (PUSPAGA) program and beneficiaries, the suitability between the PUSPAGA program and the implementing organization, and the suitability between beneficiaries and implementing organizations in an effort to implement the Child-Friendly City policy in the city of Surabaya through the PUSPAGA program. Through a descriptive qualitative method, this study provides an overview of the implementation of a program. This analysis is based on the indicators of the program implementation suitability model introduced by David C. Korten. The results of this study show that the PUSPAGA program has supported the implementation of the Child-Friendly City policy relatively well, but there are obstacles experienced due to the limitations of professional psychologists at PUSPAGA Balai RW (Rukun Warga) and the participation of the beneficiary community.